Investigation into fault tolerant capability of new modular low‐speed and high‐torque direct‐drive permanent magnet motor based on unequal span winding - Baoping Gan; Bingyi Zhang; Qiaoshan Li; Guihong Feng (IET Electric Power Applications, 2021)
Abstract Low‐speed and high‐torque direct‐drive permanent‐magnet motors have found wide applications primarily due to their outstanding performance characteristics. The special applications of these motors demand high reliability against the motor drive system, that is, the power system should have a certain level of fault tolerance. Therefore, the fault‐tolerant motor drive system has been the focus of research all over the world. Many fault‐tolerant motors can only deal with the open‐circuit fault of the winding or drive, and their capability of fault tolerance is substantially limited. When in operation, the short‐circuit fault caused by the ageing of winding insulation may result in more serious hazards than the open circuit in the winding. Such serious faults should be tolerated by the fault‐tolerant system. Moreover, the simpler maintenance or shutdown repair upon completion of fault‐tolerant operation of large‐sized fault‐tolerant motors should also be considered. Therefore, a permanent‐magnet fault‐tolerant motor with module combination stator (MCS‐PMFTSM) and unequal span winding is proposed. By changing the winding structure of the conventional motor the modular operation of the whole motor is achieved, which not only provides the motor with a high fault tolerance capacity but also reduces the downtime during repair and maintenance. In this work, the structure and operating principles of the MCS‐PMFTSM are described followed by the evaluation of the operation performances of the MCS‐PMFTSM under different fault conditions and various control strategies. The fault‐tolerant capacity of this new machine is then analysed, and the prototype is tested with a power of 12 kW and a rated speed of 100 r/min. Both theoretical analysis and test results demonstrate the outstanding operation performance and high fault tolerance of the motor.